Insulting Rhetorical Questions – Mitigators or Amplifiers? - Špago, Džemal (Respectus Philologicus, 2022)
The paper examines whether rhetorical questions (RQs) with insulting content or implications soften or intensify the insulting content that they express, as compared to corresponding direct statements with similar insulting content. The analysis is based on the results of two online surveys conducted among 276 Bosnian university students (182 and 94, respectively), who evaluated, in regard to their offensiveness, two sets of RQs and corresponding statements with insulting content or implications. Three types of insulting RQs were included in the surveys: insulting RQs without explicitly offensive terms, insulting RQs that incorporate derogatory words, and sarcastic RQs with insulting implications. The expected results were that: a) in line with Frank’s (1990) account of strengthening effects of RQs as their primary function, insulting RQs, with or without derogatory words, will function as amplifiers, and sound more offensive than corresponding declaratives; and b) sarcastic RQs, following Dews and Winner’s (1995) account of softening effects of sarcastic utterances, will function as mitigators, as compared to non-sarcastic declaratives with insulting content. The obtained results indicate that the first hypothesis cannot be verified (in spite of some indications that slight amplifying effects do exist), and the second hypothesis is completely rejected, with some likelihood that the opposite could be true.